CLINICAL AND MORPHOLOGICAL RESEARCH INTO THE ROLE OF THE TRANSCRIPTION FACTOR NEUROD1 IN VARIOUS TYPES OF PITUITARY ADENOMAS - O. M. Raspopova; L. B. Mitrofanova; B. E. Galkovsky; U. A. Tsoy; U. N. Grineva; A. A. Palcev; V. R. Rodichkina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The role of transcription factors in the pathogenesis of pituitary adenomas is extremely controversial.The aim of the study was to investigate the role of the transcription factor Neuro D1 in various types of pituitary adenomas.Materials and methods. A comparative clinico-morphological study was carried out with immunohistochemical analysis and confocal microscopy of the expression of the transcription factor NeuroD1, six adenohypophysis hormones and Ki-67 in 40 pituitary adenomas and 9 normal pituitary glands.Results. NeuroD1 was expressed in all cases and types of adenomas. The expression level of the transcription factor in adenomas was significantly different from that in the normal pituitary gland (p = 0.006). The average number of cells with expression of NeuroD1 in all tumors was higher than in the normal pituitary gland.Conclusion. NeuroD1 plays one of the key roles in the pathogenesis of pituitary adenomas, regardless of their hormonal status.